PERBEDAAN POLA MAKAN PADA BALITA STUNTING DAN TIDAK STUNTING DI KECAMATAN TEON NILA SERUA (TNS) KABUPATEN MALUKU TENGAH - Trixie Leunupun; Ani Margawati; Annastasia Ediati (Dian Nuswantoro Semarang, 2021)
Stunting is a condition that describes the growth of children due to long-term malnutrition. Stunting according to WHO is based on the index of the body length compared to age (PB/U) or height compared to the age (TB/U) with the Z-score limit of less than-2 SD. The age of toddlers is an age where child growth and development happens very quickly. In that age toddlers often experience health problems especially nutritional problems. Insufficient nutritional intake can cause stunting and can inhibit children's development. Design of observational analytic research with case-control design in toddlers aged 2-3 years. The population of this research is all toddlers who reside in the working area of Puskesmas Layeni subdistrict of Central Maluku district. Sample research is done using the Lameshow formula. The study used the ratio of 1:1 so that the number of research subjects in the case group was equivalent to the number of research subjects in the control group (i.e. 30 children per group), resulting in a total subject of 60 children. Analysis of the data used to see the difference between variables using the chi-square test. Variable dependent events are stunting and independent dietary variables. The results of the chi-square test show that there is no difference between the diet (the level of energy and protein adequacy) in a stunting toddler and not stunting the value (p > 0.05). The conclusion of the diet (adequacy of energy and protein) respectively in the group of cases is not too much of a significant difference. But in the control group more toddlers with good energy and protein adequacy levels. Keywords: toddler, diet, stunting